HIV-Associated Neurocognitive Impairment in the Modern ART Era: Are We Close to Discovering Reliable Biomarkers in the Setting of Virological Suppression? - Bandera, Alessandra; Taramasso, Lucia; Bozzi, Giorgio; Muscatello, Antonio; Robinson, Jake A.; Burdo, Tricia H.; Gori, Andrea (Frontiers in aging neuroscience, 2019)
The prevalence of the most severe forms of HIV-associated neurocognitive disorders (HAND) is decreasing due to worldwide availability and high efficacy of antiretroviral treatment (ART). However, several grades of HIV-related cognitive impairment persist with effective ART and remain a clinical concern for people with HIV (PWH). The pathogenesis of these cognitive impairments has yet to be fully understood and probably multifactorial. In PWH with undetectable peripheral HIV-RNA, the presence of viral escapes in cerebrospinal fluid (CSF) might explain a proportion of cases, but not all. Many other mechanisms have been hypothesized to be involved in disease progression, in order to identify possible therapeutic targets. As potential indicators of disease staging and progression, numerous biomarkers have been used to characterize and implicate chronic inflammation in the pathogenesis of neuronal injuries, such as certain phenotypes of activated monocytes/macrophages, in the context of persistent immune activation. Despite none of them being disease-specific, the correlation of several CSF cellular biomarkers to HIV-induced neuronal damage has been investigated. Furthermore, recent studies have been evaluating specific microRNA (miRNA) profiles in the CSF of PWH with neurocognitive impairment (NCI). The aim of the present study is to review the body of evidence on different biomarkers use in research and clinical settings, focusing on PWH on ART with undetectable plasma HIV-RNA.